Quest for relevance: Whither the ASEAN Charter in shaping a shared regional identity and values - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2018)
Promulgated in 2007, the Charter of the Association of Southeast Asian Nations (ASEAN) reaffirms ASEAN’s longstanding policy of non-interference in member-states’ internal affairs and the retention of consultation and consensus as fundamental tenets of decision-making in ASEAN. This essay considers the role of soft law in the interpretation and development of the ASEAN Charter. It also considers whether the Charter will help ASEAN achieve integration as well as promote democracy, human rights and development in an immensely diverse region comprising half a billion people. The essay argues that although the Charter is a binding legal instrument, the text enables a significant degree of flexible interpretation and room for negotiation. This inherent flexibility is an encapsulation of the ASEAN way, rendered as a principle of ASEAN regional governance, and continues to be the foundation for the common rules of engagement. As an inherently soft law document, the Charter is better positioned to socialize ASEAN member-states in imbibing the desired values and norms, and helps generate trust. This integrative approach is more sustainable than a plethora of treaty law or an approach that ostensibly and significantly pools sovereignty. Such a crafting of the Charter promotes constitutive processes such as persuasion, learning, cooperation and socialization, while also providing some assurance that ASEAN, as a legal personality, is not attempting to derogate from the ‘ASEAN Way’ but evolving sensitively to the changing landscape. The Charter is a legal-political nudge requiring ASEAN to calibrate its actions, policies and its understanding of sovereignty to be in line with the prevailing normative framework globally.